Positive response to niraparib in chemo-refractory patients with metastatic appendiceal mucinous adenocarcinoma harboring ATM mutations: A case report - Wang, Junhui; He, Huijuan; Xu, Wansu; Chen, Jianxin (Frontiers in Oncology, 2023)
Background Appendiceal mucinous adenocarcinoma, one kind of specific colorectal cancer, is lowly prevalent and rarely diagnosed in clinical practice. In addition, there have been limited standard treatment strategies established for patients with appendiceal mucinous adenocarcinoma, especially with metastatic disease. The regimens for colorectal cancer, which were adopted in appendiceal mucinous adenocarcinoma, usually resulted in limited effectiveness. Case presentation Herein, we presented a case of chemo-refractory patient with metastatic appendiceal mucinous adenocarcinoma harboring ATM pathological mutation of exon 60, c.8734del, p.R2912Efs*26, and who has achieved a persistent response to salvage treatment of niraparib, with disease control time that reached 17 months and still in extension. Conclusions We supposed that appendiceal mucinous adenocarcinoma patients harboring ATM pathological mutations may respond to the treatment of niraparib, even without a homologous recombination deficiency (HRD) status; however, it needs further confirmation in a larger cohort.